Real-Time Monitoring of Driver’s Biometrics to Prevent Multi-Vehicle Chain Collisions Caused by Impending Medical Emergencies - V.N. Kavitha, K; Kesarwani, Kanishak; M. Pranav, S; Noah, Tanish (International Journal of Engineering and Technology, 2018)
Smart healthcare systems are essentially going to become an inevitable part of our day to day activities. Sophisticated health monitoring devices will be used to provide a safer and less accident-prone society. Their use in active accident mitigation and management will extend, in the coming years, to not only our home atmosphere but will also include manufacturing, transportation, work-place and agricultural milieu. As a matter of fact, real time healthcare monitors have been introduced in some high-end, expensive luxury cars such as Mercedes-Benz and Tesla. The design proposed is a low-cost and affordable, continuous healthcare monitoring system which aims to extend the use Internet of Things (IoT) to vehicular systems. It is designed to detect anomalies in the driver’s health conditions and take preventive actions to prevent road accidents. These actions include steadily reducing the vehicle’s speed and ultimately stopping it. Simultaneously, an alarm or warning is relayed to the nearby vehicles of the impending emergency that has occurred, thus cautioning them of a possible accident. An emergency message is spontaneously relayed to the concerned medical personnel and to the emergency contacts–relatives of the driver.